User Attitude as a Mediating Variable in Technology Acceptance: Evidence from a Government Statistics Application - Kartiko, Heru; Ardianto, Yusaq Tomo; Natsir, Mokhamad (University Merdeka Malang, 2025)
This study examines user acceptance of the Mboistats application developed by the Malang Statistics Bureau by applying the Technology Acceptance Model (TAM). Specifically, it analyzes the effects of perceived ease of use and perceived usefulness on actual system usage, with user attitude serving as a mediating variable. Data were collected through an online questionnaire distributed to 100 users and analyzed using path analysis. The results indicate that perceived ease of use and perceived usefulness have significant direct effects on user attitude and actual usage. However, user attitude does not mediate the relationship between perceived ease of use or perceived usefulness and actual usage. These findings suggest that when a digital application offers clear and measurable benefits, users tend to adopt the system directly without relying on attitudinal evaluation. This study contributes to the technology acceptance literature by providing empirical evidence from a government statistics application and highlights the importance of enhancing usability and perceived benefits to promote adoption of public sector digital services.